Karakter Visual dan Gaya Ilustrasi Naskah Lama di Jawa Periode 1800-1920 - Nuning Yanti Damayanti (ITB Journal Publisher, LPPM ITB, 2008)
The tradition of illustrated writing and drawing was found in the old manuscripts of Indonesia. Some parts of those old manuscripts show unique illustrations depicting local identity of Nusantara. It is thought that the manuscript reflects societal culture of thinking as well as aesthetic achievement of visual art. The illustrations of those old Javanese manuscripts were well documented and represented in various visual styles, drawing methods, themes, and visualized objects; even though their visual concepts practically resembles to each other. The presented paper discusses the visual character and styles of illustrations found in the old manuscripts of Java within the year of 1800-1920. The illustration in those old Javanese manuscripts shows continuous correlation to the visual style of the past era and the present. Thus, it emboldens the characteristics of Indonesian visual states. It reflects structured illustration and visual style as well as expressive symbols of the Javanese society. Illustration of the old Javanese manuscript in the year 1800-1920 showed some changes and uniqueness in its visuals, comprising interaction between animism in the Pre-Hinduism era, cultural paradigm of Hinduism-Budhism, Islamic beliefs, and Colonialism. Having observed the visual illustration in the old Javanese manuscripts, it can be deduced that their styles are characterized as decorative, naturalistic, realistic, simple, and deformed.